Regioselective activation of benzocyclobutenones and dienamides lead to anti-Bredt bridged-ring systems by a [4+4] cycloaddition - Jianyu Zhang (Nature Portfolio, 2021)
Bridgehead carbon benzofused-bridged ring systems have previously not been accessible via synthetic approaches. Here, the authors report a formal type-II [4 + 4] annulation approach that provides fully sp2-carbon embedded anti-Bredt bicyclo[5.3.1] skeletons through the Rh-catalyzed C1–C8 activation of benzocyclobutenones and their coupling with pedant dienamides.